The Paleoecological Record of 6 ka BP Climate in the Canadian Prairie Provinces - Vance, Robert; Beaudoin, Alwynne; Luckman, Brian (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1995)
ABSTRACTSynthesis of available paleoecological studies in the Prairie provinces of Canada indicates that although the peak in postglacial aridity that characterized early Holocene climate of the western foothills and plains had passed, conditions remained warmer and drier than present throughout the region ca. 6000 yr BP Compared to today, treeline elevations were higher and alpine glaciers were reduced in size in the Rocky Mountains, lake levels were lower over much of the Interior Plains, and the grassland and boreal forest ecozones extended north of their present positions. Forest fires were more prevalent ca. 6000 yr BP than they are today, aiding westward migration of jack pine (Pinus banksiana) through the boreal forest and increasing the area occupied by grassland in boreal and montane forest regions. Attempts to quantify the magnitude of 6 ka temperature and precipitation differences have produced variable results, but suggest that mean annual temperature was 0.50°C to 1.50°C higher than today (summer temperature may have been up to 3°C higher) and mean annual precipitation was reduced by 65 mm (or summer precipitation was reduced by 50 mm), compared to present. The nature and scale of these changes suggests that a vigorous zonal atmospheric circulation pattern, similar to that of the 1930s but shifted northward, prevailed at 6 ka.